MENGELOLA EVENT THE 22ND ASEAN ECONOMIC COMMUNITY COUNCIL 2023: KONTRIBUSI PROJECT OPERATIONAL & PRODUCTION EVENT OFFICER DI KOMPAS GRAMEDIA- UNIT DYANDRA PROMOSINDO - Mumtaz, Syahnaez Zahira; Yudih, Dadang; Susanti, Keuis Hera (El-Ecosy : Jurnal Ekonomi dan Keuangan Islam, 2024)
Event The 22nd ASEAN Economic Community Council 2023 merupakan acara penting yang diselenggarakan di Hotel Indonesia Kempinski Jakarta oleh Kementerian Ekonomi Republik Indonesia dan Dyandra Promosindo. Dalam mengelola acara tersebut, Project Operational & Production Event Officer memegang peran penting. Tujuan dari penelitian ini adalah untuk mengetahui kontribusi Project Operational & Production Event Officer dalam mengelola acara tersebut. Metode yang digunakan dalam penelian ini adalah deskriptif kualitatif dengan Teknik pengumpulan data melalui wawancara dan observasi. Hasil penelitian menunjukkan bahwa Project Operational & Production Event Officer memberikan kontribusi yang signifikan dalam mengelola acara the 22nd ASEAN Economic Community Council 2023. Kontribusi tersebut meliputi perencanaa, pengorganisasian, pelaksanaan, dan evaluasi acara. Dalam perencanaan acara, Project Operatial  Production Event Officer bertanggung jawab dalam menentukan konsep acara, membuat timeline, dan mengatur anggaran. Selain itu, dalam pelaksanaan acara, Project Operational & Production Event Officer juga bertanggung jawab dalam mengatur teknis acara, seperti pencahayaan, suara, dan dekorasi. Kesimpulannya, Project Operational & Production Event Officer memberikan kontribusi yang signifikan dalam mengelola acara the 22nd ASEAN Economic Community Council 2023 di Hotel Indonesia Kempinski Jakarta yang diselenggarakan oleh Kementerian Ekonomi Republik Indonesia dan Dyandra Promosindo.ABSTRACTThe 22nd ASEAN Economic Community Council 2023 is an important event organized at Hotel Indonesia Kempinski Jakarta by the Ministry of Economy of the Republic of Indonesia and Dyandra Promosindo. In managing the event, Project Operational & Production Event Officer plays an important role. The purpose of this research is to find out the contribution of Project Operational & Production Event Officer in managing the event. The method used in this research is descriptive qualitative with data collection techniques through interviews and observations. The results showed that the Project Operational & Production Event Officer made a significant contribution in managing The 22nd ASEAN Economic Community Council 2023 event. These contributions include planning, organizing, implementing, and evaluating the event. In event planning, the Project Operational Production Event Officer is responsible for determining the event concept, creating a timeline, and managing the budget. In addition, in the implementation of the event, the Project Operational & Production Event Officer is also responsible for organizing the technical aspects of the event, such as lighting, sound, and decorations. In conclusion, the Project Operational & Production Event Officer made a significant contribution in managing The 22nd ASEAN Economic Community Council 2023 event at Hotel Indonesia Kempinski Jakarta organized by the Ministry of Economy of the Republic of Indonesia and Dyandra Promosindo.